2018
DOI: 10.1075/itl.00013.nor
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary knowledge and listening comprehension at an intermediate level in English and French as foreign languages

Abstract: The present study aims to replicate Stæhr’s (2009) study on the relationship between vocabulary knowledge and listening comprehension. To explore the generalizability of Stæhr’s findings, two experiments were conducted. However, the study changed the population (Flemish learners) and proficiency level of the materials in the first experiment (intermediate) and also the language in the second experiment (French). Our results generally confirm Stæhr’s findings. We also found a positive correlation between vocabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…No studies to date that we are aware of explore the effects of listening skills on vocabulary learning through video viewing. Previous research examining the relationship between vocabulary and listening has shown that vocabulary size is significantly, although modestly, correlated with listening comprehension (Noreillie et al 2018;Staehr 2009). This also holds true as far as the relationship between vocabulary depth and listening comprehension is concerned (Staehr 2009).…”
Section: Literature Reviewmentioning
confidence: 78%
“…No studies to date that we are aware of explore the effects of listening skills on vocabulary learning through video viewing. Previous research examining the relationship between vocabulary and listening has shown that vocabulary size is significantly, although modestly, correlated with listening comprehension (Noreillie et al 2018;Staehr 2009). This also holds true as far as the relationship between vocabulary depth and listening comprehension is concerned (Staehr 2009).…”
Section: Literature Reviewmentioning
confidence: 78%
“…Also, the fact that none of AU's students has mastered 3.000 word-families, and only about 4% of BU's students have mastered the level is alarming. Knowing limited words from most frequent the first 1.000 word-families to the third 1.000 word-families will cause the students Noreillie et al (2018) have found, knowing the 1 st 1.000 and the 2 nd 1.000 most frequent word-family is crucial for L2 learners because they equal 91% and 97% coverage of a text. In the same line, Nation (2006) has stated that 86 % of the running words in the texts are from the 1 st 1.000 word-families and the 2 nd 1.000 word-families, and the students need a 98% threshold to be able to read a wide range of texts.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous researches have found that high-frequency words are important. Recent research of Noreillie et al (2018) has revealed that knowing the first 1.000 and the second 1.000 most frequent word-family is crucial for L2 learners because they equal 91% and 97% coverage of a text. Peters and Webb (2018) have stated that when someone wants to understand 90% of the running words in the documentary, he/she needs to have 90% coverage of the most frequent 2.000 words.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if students know 95 out of the 100 running words in a given text, the lexical coverage figure would be 95%. In recent years, the relationship between lexical coverage and listening comprehension has been the focus of many studies (e.g., Staehr, 2009;van Zeeland and Schmitt, 2013;Noreillie et al, 2018;Giordano, 2021). Findings from these studies typically suggest contrasting lexical thresholds for adequate listening comprehension.…”
Section: Lexical Coverage and Listening Comprehensionmentioning
confidence: 99%